Newly acquired complete right bundle branch block early after heart transplantation is associated with lower survival. (2nd July 2021) - Rahm, Ann‐Kathrin; Helmschrott, Matthias; Darche, Fabrice F.; Thomas, Dierk; Bruckner, Tom; Ehlermann, Philipp; Kreusser, Michael M.; Warnecke, Gregor; Frey, Norbert; Rivinius, Rasmus
Abstract: Aims: Right bundle branch block (RBBB) after heart transplantation (HTX) is a common finding, but its impact on post‐transplant survival remains uncertain. This study investigated the post‐transplant outcomes of patients with complete RBBB (cRBBB) ≤ 30 days after HTX. Methods: This registry study analysed 639 patients receiving HTX at Heidelberg Heart Center between 1989 and 2019. Patients were stratified by diagnosis of cRBBB ≤ 30 days after HTX. Analysis included recipient and donor data, medication, echocardiographic features, graft rejections, atrial fibrillation, heart rates, permanent pacemaker implantation and mortality after HTX including causes of death. Results: One hundred thirty‐nine patients showed cRBBB ≤ 30 days after HTX (21.8%), 20 patients with pre‐existing cRBBB in the donor heart (3.2%) and 119 patients with newly acquired cRBBB (18.6%). Patients with newly acquired cRBBB had a worse 1‐year post‐transplant survival (36.1%, P  < 0.01) compared with patients with pre‐existing cRBBB (85.0%) or without cRBBB (86.4%), along with a higher percentage of death due to graft failure ( P  < 0.01). Multivariate analysis indicated cRBBB ≤ 30 days after HTX as significant risk factor for 1‐year mortality after HTX (HR: 2.20; 95% CI: 1.68–2.87; P < 0.01). Secondary outcomes showed a higher rate of an enlarged right atrium ( P  = 0.01), enlarged right ventricle ( P  < 0.01), reduced right ventricular function ( P  < 0.01), 30‐day atrial fibrillation ( P  < 0.01) and 1‐year permanent pacemaker implantation ( P  = 0.02) in patients with cRBBB after HTX. Conclusions: Newly acquired cRBBB early after HTX is associated with increased post‐transplant mortality.